Deciphering the correlations between aging and constipation by metabolomics and network pharmacology - Liu, Xiaojie (Aging (Albany NY), 2021)
From the points of view of phenomena and experience, aging and constipation are inextricably correlated. However, experimental support and underlying mechanisms are still lacking. The purpose of this study is to explore the relationships between aging and constipation from the perspectives of fecal metabolites and network pharmacology. The behavioral analyses of aging and constipation were carried out on both aging rats and constipation rats. We found that aging rats exhibited not only significant aging behaviors but also significant constipation behaviors, while constipation rats exhibited both significant constipation and aging behaviors. Additionally, fecal metabolomics was carried out and found that 23 metabolites were aging-related and 22 metabolites were constipation-related. Among them, there were 16 differential metabolites in common with 11 metabolic pathways. Network pharmacology was applied to construct the target-pathway network of aging and constipation, revealing that pathway in cancer was the most associated signaling pathway. The current findings will provide not only a novel perspective for understanding aging and constipation, but a theoretical association and understanding the traditional Chinese medicine theory and the Western medicine theory about aging and constipation, as well as support for the clinical research and development of medicine related to constipation in the elderly.